Текстові втілення архетипів філософського дискурсу (на матеріалі англійської мови) - Малиновська, І.В. (Лінгвістика ХХІ століття: нові дослідження і перспективи, 2012)
The paper discusses the linguistic understanding of the concept of archetype at the backdrop of semiotic approach. Hypothesized has been the possibility of linguistic identification of philosophical archetypes in text and discourse. Proceeding from the multidisciplinary theory of archetype in psychology, culture and consciousness and science the specificity of archetypes in philosophical discourse has been articulated. As the latter lies within the mode of philosophizing, the manifestations of the archetypes in question should be found in the cognitive structure, stylistic characteristics and lexical organization of the philosophical discourse.